Analisis kelayakan finansial usaha budidaya rumput laut (Eucheuma Denticulatum) Menggunakan Metode Longnet (Studi Kasus di Pantai Lakeba Kecamatan Betoambari Kota Baubau) - Hariyanti, Wa Ode; Kasim, Ma'ruf; A, Nurdiana (Jurnal Sosial Ekonomi Perikanan, 2021)
Eucheuma denticulatum is one of seaweed spesies that has been cultivated by some coastal communities in SE-Sulawesi using several methods. Longnet is considered an innovative method but the culture feasibility isstill unkonown. The objective of this research was to determine the financial feasibility of cultivating seaweed (E. denticulatum) using the Longnet method at Lakeba Beach, Betoambari District, Baubau City. This study was conducted using a case study method on one farmer who cultivating seaweed using longnet. Data obtained through interviews using a questionnaire, observation and documentation. Data were analyzed descriptively quantitatively based on the criteria of Net Present Value (NPV), R / C (Revenue / Cost) ratio, Payback Period (PBP), and Internal Rate of Return (IRR). The results of the feasibility analysis are indicated by an interest rate of 12.5%, with a positive NPV value of 487,690,580; R / C Ratio> 1 (1.06); PBP for 3.62 years; IRR value 41%. Based on the feasibility results, it shows that the seaweed cultivation business using the longnet method on Lakeba Beach, Betoambari District, Baubau City was financially profitable and feasible to be further developer